Analysis of Short and Long Term Effect on Government Expenditure Realization and Income Disparity Toward Poverty in Aceh Province, Indonesia - Mirza Zuhri; Abd. Jamal; Putri Bintusy Syathi (International Journal of Business, Economics, and Social Development, 2022)
Implementing the Regional Revenue and Expenditure Budget (APBD) policy and at the same time reducing income disparity is a tangible manifestation and success of local governments to keep poverty level low. This study focuses on the analyzing short-term and long-term effects of variables government expenditure realization and income disparity toward poverty in Aceh Province, Indonesia during 2010-2019 period using Auto Regressive Distributed Lag (ARDL) approach. It is found that both independent variables have no significant effect on short term but have significant effect on long term. Government expenditure realization is found significant at error level 1% while income disparity is found significant at error level 5% toward poverty in long term. Also both government expenditure realization and income disparity is found to have positive effect toward poverty in long term. Based on these findings it is hoped the policy maker will able to formulate a strategic plan to reduce poverty rate in Aceh Province, Indonesia.